Minimal-invasive Stabilisierung bei thorakolumbalen osteoporotischen Frakturen - Schnake, Klaus John; Scheyerer, Max Josef; Spiegl, Ulrich Josef Albert; Perl, Mario; Ullrich, Bernhard Wilhelm; Grüninger, Sebastian; Osterhoff, Georg; Katscher, Sebastian; Sprengel, Kai (Unfallchirurg, 2020)
Background: Minimally invasive stabilization of thoracolumbar osteoporotic fractures (OF) in neurologically intact patients is well established. Various posterior and anterior surgical techniques are available. The OF classification and OF score are helpful for defining the indications and choice of operative technique. Objective: This article gives an overview of the minimally invasive stabilization techniques, typical complications and outcome. Material and methods: Selective literature search and description of surgical techniques and outcome. Results: Vertebral body augmentation alone can be indicated in painful but stable fractures of types OF 1 and OF 2 and to some extent for type OF 3. Kyphoplasty has proven to be an effective and safe procedure with a favorable clinical outcome. Unstable fractures and kyphotic deformities (types OF 3–5) should be percutaneously stabilized from posterior. The length of the pedicle screw construct depends on the extent of instability and deformity. Bone cement augmentation of the pedicle screws is indicated in severe osteoporosis but increases the complication rate. Restoration of stability of the anterior column can be achieved through additional vertebral body augmentation or rarely by anterior stabilization. Clinical and radiological short and mid-term results of the stabilization techniques are promising; however, the more invasive the surgery, the more complications occur. Conclusion: Minimally invasive stabilization techniques are safe and effective. The specific indications for the individual procedures are guided by the OF classification and the individual clinical situation of the patient.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Augmentation; Bone cements; Classification; Pedicle screws; Spine